ANALISIS PELAKSANAAN PENGELOLAAN DANABANTUAN OPERASIONAL SEKOLAH (BOS) PADA SEKOLAH DASAR NEGERI 34/1 TERATAI - Niki Kosasih (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The purpose of this study was to determine the implementation of the management of the school operational assistance fund (BOS). This research was conducted at SDN 34./1 Teratai. The method used in this research is descriptive qualitative research method. Where the focus of this research is to describe / describe the Implementation of BOS SD Fund Management in 34 / I Teratai Public Elementary School, Muara Bulian Subdistrict, Batang Hari Regency, 2017. Data collection was carried out by observation, interviews and documentation. Based on the analysis carried out, it can be concluded that the implementation of the management of BOS funds at SDN 34 / I Teratai has been running as it should in accordance with the Responsibility instructions for the use of BOS funds in 2017 even though the management of BOS funds has been carried out as well as possible but errors and shortcomings are still found even though only a small scope such as misplaced position and tax issues and even then it does not happen again but it is not an intentional element of the BOS funds manager and the problems encountered can still be corrected and resolved properly.